W.G. Sebald's Paper Universe. - Draney, James (Journal of Modern Literature)
Late in his artistic and scholarly career, W.G. Sebald decided to eschew then-emergent modes of computational media in favor of analogue production techniques. Sebald himself often remarked on his encounters with media, both new and old, expressing a consistent interest in the materiality of writing. In his own artistic practice, he preferred the process of handwriting to what he called the tyranny of "PC Perfectionism." Scenes of writing, and the technologies of pen, paper, and pencil, appear regularly throughout Sebald's corpus, especially in The Rings of Saturn (1995) and Austerlitz (2001). These elegiac encounters with residual technologies informed Sebald's literary aesthetic. The novel Austerlitz, in particular, foregrounds media history and the evolution of modes of writerly work. In this novel, written in the shadow of new modes of digital writing that were becoming ubiquitous at the end of the twentieth century, Sebald's poetics of media obsolescence emerges as key preoccupation in his aesthetic project.